Numerical Modeling of the Degradation of the Normal Stress Under Large Number of Shearcycles - Bellayoune, Assia; Messast, Salah; Boulon, Marc (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The evaluation of friction is an important element in the verification of stability and the determination of the bearing capacity of piles. In the case of cyclic stress, the soil-pile interface has a relaxation which corresponds to a fall in the horizontal stress which represents the normal stress at the lateral surface of the pile. This paper presents an explicit formulation to express the degradation of the normal stress after a large number of shear cycles as a function of cyclic parameters.
Keywords: bearing capacity of piles; normal stress; shear; friction; degradation; numerical modeling; nośność pali; naprężenie normalne; tarcie; ścinanie; degradacja; modelowanie numeryczne